Continuity and change in sexual attitudes: A cross-time comparison of tolerance towards non-traditional relationships. Issue 4 (November 2017) - Watt, Laura; Elliot, Mark
This article explores how attitudes towards different types of sexual relationships have changed over time. Data from the National Survey of Sexual Attitudes and Lifestyles (1990, 2000 and 2010) are used to investigate whether people living in Britain have become more (or less) tolerant of one night stands, same-sex relationships and extra-marital relations, and whether any observed changes result from period or cohort effects. While attitudes towards same-sex relationships became far more tolerant between 1990 and 2010, the pattern was not the same for one night stands or extra-marital relationships. Based upon these results the article argues that the proposition made by individualisation theory regarding the loosening of traditional norms is far too simplistic when talking about change over time in intimate life. It is argued instead that a more nuanced theory of social change is required, consistent with the finding that some norms are strengthening rather than weakening. The article also claims that certain elements of individualisation theory might in fact be consistent with the strengthening of those norms.